2016
DOI: 10.3171/2015.12.spine15366
|View full text |Cite
|
Sign up to set email alerts
|

Microscope-assisted endoscopic interlaminar ligation of spinal arteriovenous fistulas: technical note

Abstract: Spinal dural arteriovenous fistulas (SDAVFs) are the most common type of spinal arteriovenous malformations, and microsurgical ligation is the treatment modality most frequently used for these lesions. Developments in endoscopic techniques have made endoscopy an even less invasive alternative to routine microsurgical approaches in spine surgery, but endoscopic management of SDAVF or other intradural spinal lesions has not been reported to date. The authors describe the use of a microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…For this reason, some centres are implementing novel technologies (e.g. microscope-assisted endoscopic techniques in order to reduce the risk of complications) [17].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, some centres are implementing novel technologies (e.g. microscope-assisted endoscopic techniques in order to reduce the risk of complications) [17].…”
Section: Discussionmentioning
confidence: 99%
“…As for intradural lesion, case report revealed that full-endoscopic approach may be a potential alternative for the resection of intradural extramedullary tumor 62 or the ligation of spinal dural arteriovenous fistula. 63 However, indications are limited to small size tumors without significant nerve roots or spinal cord compression. It is challenging to debulk and detatch the large-size tumor with full-endoscopic technique under limited visualization.…”
Section: Potential For Future Expansionmentioning
confidence: 99%